2017
DOI: 10.1007/s12105-017-0789-y
|View full text |Cite
|
Sign up to set email alerts
|

Update from the 4th Edition of the World Health Organization Classification of Head and Neck Tumours: Mucosal Melanomas

Abstract: therapeutic targetability. The recognition of the distinct genetic changes in this subgroup of melanomas means that therapy advances in cutaneous melanomas may not translate to head and neck mucosal melanomas and clinical trials specific to this subgroup of patients are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
103
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 63 publications
(105 citation statements)
references
References 39 publications
1
103
1
Order By: Relevance
“…However, perineural invasion was not observed microscopically. Cellular morphology of sinonasal mucosal melanoma included epithelioid, plasmacytoid, spindled, undifferentiated and mixed types [1,19]. Cellular morphology didn't correlate with DSS (data not shown).…”
Section: Clinicopathologic Features and Survival Of Sinonasal Mucosalmentioning
confidence: 92%
See 4 more Smart Citations
“…However, perineural invasion was not observed microscopically. Cellular morphology of sinonasal mucosal melanoma included epithelioid, plasmacytoid, spindled, undifferentiated and mixed types [1,19]. Cellular morphology didn't correlate with DSS (data not shown).…”
Section: Clinicopathologic Features and Survival Of Sinonasal Mucosalmentioning
confidence: 92%
“…Therefore, in the 7 th edition of AJCC Cancer Staging Manual, development of sinonasal mucosal melanoma was categorized into four stages, namely stages III, IVA, IVB and IVC. According to the 8 th edition of AJCC Cancer Staging Manual, 5-year survival rates of nasal and sinonasal mucosal melanoma were 15-30% and 0-5%, respectively [1]. In our previous study, we also found that, as lethal as sinonasal melanoma, approximately 10% of patients could survive for over 5 years without metastasis.…”
Section: Introductionmentioning
confidence: 89%
See 3 more Smart Citations